Duck days - Leach, Sara, 1971- (Slug Days Stories., 2020)
"Third-grader Lauren, who has Autism Spectrum Disorder, is practising the skill of 'going with the flow, ' but finds that difficult when she learns that her best friend Irma has made another friend, Jonas. Meanwhile, Lauren is dreading a looming mountain bike day at school. Her classmate Ravi teases anyone with training wheels like hers. Lauren feels better about Jonas when he tells her how important she is to Irma, and he helps her face the mountain bike day by imagining unkind words flowing off her the way water flows off a duck."--